Design and Construction of Lifting Beams - Ricker, David T. (Engineering Journal, 1991)
Lifting beams (also known as spreader beams) are used to assist in the hoisting process. Most erectors and riggers accumulate an assortment of lifting beams during the course of time. This arrangement provides two places of attachment to the object being lifted, thus avoiding the possibility of overstressing if a single attachment were used. This also allows for a straight pull on the object rather than an oblique pull as would result if chokers alone were used. This is sometimes important to minimize unwanted erection stresses or to prevent reversal of stress in certain portions of the lifted object. For instance, the oblique pull in Fig. 2A may cause excess compression in the top chord of the truss at a time when that chord is laterally unbraced. The arrangement in Fig. 2B will help to alleviate this tendency and optimum choker locations can be chosen to minimize the stresses during the erection phase. Figure 1B illustrates the type of lifting beam that might be employed in Fig. 2B. The beam has multiple holes at the underside for attachment to the object to be hoisted, thus providing a large range of adjustment. This arrangement will also prevent the object from tilting excessively should the hook be slightly off-center of the balance point.